Sweat characteristics and fluid balance responses during two heat training camps in elite female field hockey players - Goods, P. S.; Wall, B.; Galna, B.; McKay, A. K.; Jennings, D.; Peeling, P.; Watson, G. (International Journal of Sport Nutrition and Exercise Metabolism, 2024)
We examined the sweat characteristics and fluid balance of elite female field hockey players during two heat training camps. Fourteen elite female field hockey players from the Australian national squad participated in two heat training camps held ~6 months apart, following winter- (Camp 1) and summer-based training (Camp 2). Daily waking body mass (BM) and urine specific gravity (USG) were collected, along with several markers of sweat and fluid balance across two matches per camp. There was a 19% mean reduction in estimated whole-body sweat sodium concentration from Camp 1 (45.8 ± 6.5 mmol/L) to Camp 2 (37.0 ± 5.0 mmol/L; p < .001). Waking urine specific gravity = 1.020 was observed in 31% of samples, with no significant differences in mean urine specific gravity or BM between camps (p > .05), but with substantial interindividual variation. Intramatch sweat rates were high (1.2-1.8 L/hr), with greater BM losses in Camp 1 (p = .030), resulting in fewer players losing =2% BM in Camp 2 (0%-8%), as compared with Camp 1 (36%-43%; p = .017). Our field data suggest that elite female field hockey players experience substantial sweat losses during competition in the heat regardless of the season. In agreement with previous findings, we observed substantial interindividual variation in sweat and hydration indices, supporting the use of individualized athlete hydration strategies.